Celecoxib Enhances the Efficacy of Low-Dose Antibiotic Treatment against Polymicrobial Sepsis in Mice and Clinical Isolates of ESKAPE Pathogens - Annamanedi, Madhavi; Varma, Gajapati Y. N.; Anuradha, K.; Kalle, Arunasree M. (Frontiers in Microbiology, 2017)
Treatment of multidrug resistant bacterial infections has been a great challenge globally. Previous studies including our study have highlighted the use of celecoxib, a non-steroidal anti-inflammatory drug (NSAID) in combination with antibiotic has decreased the minimal inhibitory concentration (MIC) to limit Staphylococcus aureus infection. However, the efficacy of this combinatorial treatment against various pathogenic bacteria is not determined. Therefore, we have evaluated the potential use of celecoxib in combination with low doses of antibiotic in limiting Gram positive and negative bacteria in vivo in murine polymicrobial sepsis developed by cecum-ligation and puncture (CLP) method and against clinically isolated human ESKAPE pathogens. The in vivo results clearly demonstrated a significant reduction in the bacterial load in different organs and in the inflammatory markers such as COX-2 and NF-κB via activation of SIRT1 in mice treated with imipenem, a choice of antibiotic for polymicrobial sepsis treatment. Combinatorial treatment of ampicillin and celecoxib was effective on clinical isolates of ESKAPE pathogens, 45% of tested clinical isolates showed more than 50% reduction in the colony forming units when compared to ampicillin alone. In conclusion, this non-traditional treatment strategy might be effective in clinic to reduce the dose of antibiotic to treat drug-resistant bacterial infections.